2020
DOI: 10.1093/ajcp/aqaa059
|View full text |Cite
|
Sign up to set email alerts
|

CALIPER Hematology Reference Standards (I)

Abstract: Objectives Accurate hematologic test interpretation based on normative reference standards is critical to ensure appropriate clinical decision making. However, healthy pediatric reference data for most hematology parameters are lacking. To address this gap, this study establishes age- and sex-specific hematologic reference standards in the Canadian Laboratory Initiative on Pediatric Reference Intervals (CALIPER) cohort of healthy children and adolescents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 24 publications
9
16
0
Order By: Relevance
“…These age-related trends have been previously observed and are suggested to be due to immune system immaturity and differential distribution of lymphocyte subsets from early life to adulthood. 9,10,[13][14][15] No sex-specific differences were observed in our pediatric cohort for leukocyte parameters. Previous studies have reported conflicting findings, with some demonstrating statistically significant elevations in neutrophil counts in adolescent females.…”
Section: Caliperdatabaseorg)mentioning
confidence: 61%
See 4 more Smart Citations
“…These age-related trends have been previously observed and are suggested to be due to immune system immaturity and differential distribution of lymphocyte subsets from early life to adulthood. 9,10,[13][14][15] No sex-specific differences were observed in our pediatric cohort for leukocyte parameters. Previous studies have reported conflicting findings, with some demonstrating statistically significant elevations in neutrophil counts in adolescent females.…”
Section: Caliperdatabaseorg)mentioning
confidence: 61%
“…10 Platelet counts consistently decreased throughout the pediatric age range in concordance with published studies. 6,10,[13][14][15] However, variation was observed in quantitative upper and lower reference limits across studies. Specifically, Canadian studies in the CALIPER cohort have established similar RIs of 170-380, 173-361, and 190-388 Â 10 9 /L on the Beckman DxH900, Sysmex XN3000, and Mindray BC-6800Plus in adolescents.…”
Section: Caliperdatabaseorg)mentioning
confidence: 99%
See 3 more Smart Citations